2022
DOI: 10.1111/ases.13052
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic dome resection for pediatric nonparasitic huge splenic cyst safely performed using indocyanine green fluorescence and percutaneous needle grasper

Abstract: Introduction: In recent years, dome resection, which preserves the splenic immunological function, has been the primary technique used to treat splenic cysts. We herein report a surgical technique using a needle grasper and indocyanine green (ICG) fluorescence to perform dome resection of a huge nonparasitic splenic cyst in a pediatric patient. Patient and Surgical Technique: A 13-year-old girl was incidentally diagnosed with a splenic cyst during follow-up for scoliosis. Abdominal enhanced computed tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Splenic cysts: Dome resection for splenic cysts allows for the preservation of splenic immunological function and has become the primary technique to treat splenic cysts. Masuya et al [ 82 ] reported the successful use of ICG fluorescence to assess for the thinning area of the cyst to be punctured. This is beneficial to allow preservation of normal parenchyma and avoid unnecessary splenectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Splenic cysts: Dome resection for splenic cysts allows for the preservation of splenic immunological function and has become the primary technique to treat splenic cysts. Masuya et al [ 82 ] reported the successful use of ICG fluorescence to assess for the thinning area of the cyst to be punctured. This is beneficial to allow preservation of normal parenchyma and avoid unnecessary splenectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Another case involved a non-parasitic huge splenic cyst measuring 170 mm × 140 mm × 140 mm, where dome resection was safely performed using indocyanine green fluorescence and percutaneous needle grasper. This approach effectively preserved the splenic immunological function [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…ICG fluorescence imaging significantly enhances surgical precision across pediatric surgery, offering detailed visualization of anatomical structures with minimal complications, low costs, and an easy learning curve [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Icg In General Pediatric Surgerymentioning
confidence: 99%